Agriculture, Nutrition, and Health: Connecting the Dots - Pandya-Lorch, Rajul; Fritschel, Heidi; Karelina, Zhenya; Yosef, Sivan (International Food Policy Research Institute, 2012)
The agriculture, nutrition, and health nexus came to prominence in 2011. With 1 billion people continuing to suffer from food insecurity, and with vitamin and mineral deficiencies compromising the nutrition and health of billions of people, the international development community began to ask how much more could agriculture do to improve human wellbeing if it explicitly included nutrition and health goals? What kind of changes could maximize agriculture’s contribution to human health and nutrition, and how could improved human health and nutrition contribute to a more productive and sustainable agricultural system?